A polyurethane emulsion, its preparation method and application
By modifying the alumina nanoparticles, a three-dimensional space physical mesh structure is formed and the temperature response characteristics are used to solve the problem that aqueous polyurethane emulsion is easy to delaminate, condense or precipitate during storage, achieving higher storage stability and drying rate.
Patent Information
- Application Number
- CN202411376542.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-09-30
AI Technical Summary
During storage, existing aqueous polyurethane emulsions are susceptible to external factors such as temperature, pH and shear forces, resulting in the emulsion layering, coagulation or precipitation, affecting product performance and service life.
By modifying the alumina nanoparticles, they have better dispersion and uniformity in the aqueous polyurethane emulsion, and form a three-dimensional space physical network structure to reduce free movement and agglomeration of particles, while accelerating the drying process using temperature response characteristics.
The storage stability and drying rate of aqueous polyurethane emulsion are significantly improved, the emulsion layering and precipitation are avoided, and the stability of product performance and the excellent application are ensured.
Smart Images

Figure BDA0005068815220000111 
Figure BDA0005068815220000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and specifically relates to a polyurethane emulsion and a preparation method and application thereof. Background Art
[0002] Polyurethane (PU) is a type of polymer formed by the polymerization of organic monomers polyisocyanate and polyol under the action of a catalyst to produce carbamate (also known as carbamate bond, the basic structural unit of polyurethane). It has various forms and a wide range of applications.
[0003] Since polyurethane synthesized mainly by solution polymerization will release a large amount of volatile toxic gases during the synthesis and use process, it will cause immeasurable harm to human health and become a major development problem in the current polyurethane industry. Therefore, researchers have used water instead of organic solvents to prepare a new type of polyurethane - waterborne polyurethane, which greatly reduces the use of toxic organic volatiles and makes important contributions to environmental protection and human health and safety. Waterborne polyurethane refers to a type of polyurethane product that uses water as a dispersion medium. Unlike traditional solvent-based polyurethane, waterborne polyurethane uses water as the main dispersion medium, which significantly reduces the use of organic solvents, thereby greatly reducing the emission of volatile organic compounds (VOCs), which is more environmentally friendly and reduces potential harm to human health. Secondly, waterborne polyurethane can achieve similar performance to solvent-based polyurethane by adjusting the formula, including high strength, good elasticity, excellent wear resistance and chemical resistance, etc. Moreover, waterborne polyurethane can form transparent or opaque films, which have excellent adhesion, wear resistance and flexibility, and are suitable for a variety of applications such as coatings, adhesives and textile coatings.
[0004] Waterborne polyurethane is formed by dispersing or emulsifying polyurethane prepolymer in water to form an emulsion or dispersion. According to the degree of dispersion of polyurethane particles in water, three states can be formed: waterborne polyurethane solution, waterborne polyurethane dispersion and waterborne polyurethane emulsion. These three states are not only obviously different in molecular weight and particle size, but also have their own characteristics in appearance, which are easy to distinguish. Among them, the molecular weight of waterborne polyurethane solution is between 100-1000, the particle size is less than 0.001μm, and the appearance is transparent; the molecular weight of waterborne polyurethane dispersion is between 1000-200000, the particle size is between 0.001-0.1μm, and the appearance is translucent and milky; the molecular weight of waterborne polyurethane emulsion is greater than 5000, the particle size is greater than 0.1μm, and the appearance is turbid. The polyurethane emulsion is easily affected by external factors such as temperature, pH value and shear force, resulting in emulsion stratification, coagulation or precipitation, which in turn affects the performance and service life of the product. In this regard, some scholars have conducted corresponding research. For example, Chinese patent application CN117867483A discloses a chromium-free surface treatment liquid for zinc-iron alloy coated steel plate and a preparation method thereof, which mentions a preparation method of a cationic water-based polyurethane emulsion with excellent storage stability and heat resistance stability: step 1, 100 parts by mass of oligomer diol, 50-100 parts by mass of diisocyanate, 2-8 parts by mass of triethanolamine and 10-20 parts by mass of organic solvent are added to a reaction container, heated to 50-90°C, stirred for reaction for 1-3 hours, and then cooled; step 2, when the liquid temperature in the reaction container drops to 30-40°C, 5-15 parts by mass of boric acid aqueous solution are added, and the stirring reaction is continued for 20-40 minutes; step 3, 400-600 parts by mass of deionized water are added to the reaction container, stirred for emulsification, the stirring speed is 500-1000 rpm, and stirred for 20-30 minutes to obtain a cationic water-based polyurethane emulsion. The invention combines ammonium borate salt into the molecular structure of waterborne polyurethane to give the waterborne polyurethane emulsion better hydrophilicity, so that the prepared waterborne polyurethane has better stability in aqueous solution. However, since the volatility of the solvent water in the waterborne polyurethane emulsion is inherently worse than that of the organic solvent, further enhancing its hydrophilicity will prolong its drying time. Therefore, it is urgent to develop a polyurethane emulsion to solve the above technical problems. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the purpose of the present invention is to provide a polyurethane emulsion and a preparation method and application thereof. The present invention modifies aluminum oxide nanoparticles and uses them as a functional dispersing aid for aqueous polyurethane emulsion, which can not only significantly improve the storage stability of aqueous polyurethane emulsion, but also accelerate the drying process of aqueous polyurethane emulsion through its temperature response characteristics, so that the polyurethane emulsion exhibits better performance in application, and successfully overcomes the problem in the prior art that the storage stability of aqueous polyurethane emulsion is improved by enhancing the hydrophilicity of polyurethane, which leads to a decrease in the drying rate of aqueous polyurethane emulsion.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] A polyurethane emulsion comprises the following raw materials in parts by weight: 35-50 parts of polyisocyanate, 50-70 parts of polyol, 3-5 parts of chain extender, 1-2 parts of neutralizer, 200-300 parts of water, 10-20 parts of organic solvent, 0.01-0.05 parts of catalyst and 3-5 parts of functionalized aluminum oxide nanoparticles.
[0008] Furthermore, the preparation method of the functionalized aluminum oxide nanoparticles includes: dispersing aluminum oxide nanoparticles in a solvent, then adding polyvinyl alcohol and dropping an acidic catalyst to adjust the pH value to 4-5, stirring and reacting, the reaction temperature is 60-65°C, the reaction time is 3-4h, and a suspension is obtained; after the reaction, the temperature of the suspension is lowered to room temperature, then a basic catalyst is added to adjust the pH value to 7-8, and then sodium polyacrylate is added, and the reaction is stirred for 1-2h; after the reaction, the temperature is raised to 30-40°C, poly(N-isopropylacrylamide) is added, and the reaction is stirred for 1-2h to obtain functionalized aluminum oxide nanoparticles. The average particle size of the aluminum oxide nanoparticles is preferably 20-50nm.
[0009] The invention performs modification treatment on aluminum oxide nanoparticles so that the surfaces of the aluminum oxide nanoparticles have strong hydrophilicity and can form strong hydrogen bonds with water molecules. Such modification enables the aluminum oxide nanoparticles to have better dispersibility and uniformity in the aqueous polyurethane emulsion. Meanwhile, the functionalized aluminum oxide nanoparticles can form a three-dimensional spatial physical network structure in the emulsion. The network structure can "capture" the polyurethane particles at specific positions, reduce the free movement of the particles in the emulsion, prevent agglomeration and sedimentation between the particles, reduce the phase separation phenomenon in the aqueous polyurethane emulsion, and thus improve the storage stability of the aqueous polyurethane emulsion. Secondly, the hydrophilic surface of the aluminum oxide nanoparticles can increase the surface charge density thereof to generate electrostatic repulsion, thereby effectively preventing the mutual attraction and aggregation between the nanoparticles, and further improving the uniformity and stability of the aqueous polyurethane emulsion. Moreover, the modification treatment of the present invention enables the aluminum oxide nanoparticles to automatically adjust their surface properties, such as charge or hydrophilicity and hydrophobicity, under different pH environments. In an acidic environment of pH<4, the carboxylate groups (-COO-) on the surface of the functionalized aluminum oxide nanoparticles of the present invention will be converted into carboxylic acid groups (-COOH), and the charge will be reduced, so that the nanoparticles will become more hydrophobic, and the nanoparticles tend to aggregate; in an alkaline environment, the carboxylate groups (-COO-) on the surface of the functionalized aluminum oxide nanoparticles of the present invention remain in a dissociated state, carry a large amount of negative charge to form hydrophilic groups, and prevent the nanoparticles from aggregating through electrostatic repulsion, so that the nanoparticles are dispersed. This adjustment helps to maintain the stability of the aqueous polyurethane emulsion under different storage conditions (such as acidic or alkaline environments) and prevent phase separation or emulsion deterioration; and when the pH value of the aqueous polyurethane emulsion changes, the functionalized aluminum oxide nanoparticles of the present invention can also change their interaction mode and the viscosity of the aqueous polyurethane emulsion, and by controlling the rheological properties of the emulsion, the physical stability of the emulsion during storage can be further improved. Moreover, the modified functionalized alumina nanoparticles are hydrophilic below their critical temperature (about 32°C) and become hydrophobic above the critical temperature. This change can promote particle aggregation when the temperature rises and redisperse the particles when the temperature drops, thereby maintaining the stability of the nanoparticles under different temperature conditions.
[0010] It is worth mentioning that during the drying process of the aqueous polyurethane emulsion, the surface of the functionalized aluminum oxide nanoparticles of the present invention will undergo a temperature-responsive transformation as the drying temperature changes, so that a hydrophobic nanolayer is formed on the surface of the aqueous polyurethane emulsion to reduce the surface tension of the aqueous polyurethane emulsion, thereby enhancing the hydrophobicity of the aqueous polyurethane emulsion, thereby accelerating the volatilization rate of water in the aqueous polyurethane emulsion. As the temperature rises, the aluminum oxide nanoparticles become hydrophobic, prompting water to be discharged from the aqueous polyurethane emulsion faster, thereby increasing the drying speed. This successfully overcomes the problem in the prior art that the storage stability of the aqueous polyurethane emulsion is improved by enhancing the hydrophilicity of polyurethane, which leads to a decrease in the drying rate of the aqueous polyurethane emulsion.
[0011] Furthermore, the acidic catalyst is HCl; and the alkaline catalyst is NaOH.
[0012] HCl, as a strong acid, can quickly and effectively reduce the pH value of the reaction solution to the target range. At the same time, it can provide sufficient hydrogen ion concentration to promote the activation of hydroxyl groups on the surface of aluminum oxide nanoparticles, improve the surface activity of aluminum oxide nanoparticles, and thus help polyvinyl alcohol to adsorb and fix on the surface of aluminum oxide nanoparticles, making the functional modification more thorough and uniform. As a strong base, NaOH can quickly neutralize the acidity in the solution after addition and adjust the pH value to the target range. This process is critical for the introduction and further reaction of sodium polyacrylate. In this alkaline environment, the carboxyl group (-COOH) of sodium polyacrylate is more easily deprotonated into carboxylate (-COO-), which makes it easier to adsorb on the surface of aluminum oxide nanoparticles, forming a stable negative charge layer, increasing the stability and uniform dispersion of the particles in the solution.
[0013] Furthermore, the mass ratio of the aluminum oxide nanoparticles to polyvinyl alcohol, sodium polyacrylate, and poly(N-isopropylacrylamide) is (4-7):(2-3):(1-1.5):(1-1.5).
[0014] The above ratio setting ensures that the modifier can form a multilayer structure on the surface of aluminum oxide nanoparticles, and can accurately control the functionalization degree and active site density of the surface of aluminum oxide nanoparticles. Polyvinyl alcohol provides a preliminary stable substrate to enhance the hydrophilicity of the particles; sodium polyacrylate further stabilizes aluminum oxide nanoparticles by providing more carboxylic acid groups and provides a charge barrier; and poly (N-isopropylacrylamide) gives the particles temperature response characteristics. This layered design can give full play to the functions of different modifiers, thereby improving the overall performance of aluminum oxide nanoparticles. Among them, a higher proportion of polyvinyl alcohol can increase the carboxyl density on the surface of aluminum oxide nanoparticles, increase the negative charge density of aluminum oxide nanoparticles, and enhance the electrostatic stability of the emulsion; and the appropriate proportion of poly (N-isopropylacrylamide) can give aluminum oxide nanoparticles excellent temperature response characteristics, so that they show controllable response behavior during use. By balancing the amount of each component, the high dispersibility and stability of aluminum oxide nanoparticles can be achieved, while enhancing their responsiveness in different environments.
[0015] Furthermore, the solvent in the preparation method of the functionalized aluminum oxide nanoparticles is ethanol; the dosage ratio of the aluminum oxide nanoparticles to the solvent is 1 g: 10-15 mL.
[0016] Furthermore, the method for preparing the functionalized aluminum oxide nanoparticles further includes the steps of pre-treatment and post-treatment of the aluminum oxide nanoparticles;
[0017] The aluminum oxide nanoparticle pretreatment step comprises: dispersing the aluminum oxide nanoparticles in deionized water, treating them with an ultrasonic processor for 30 minutes, wherein the ultrasonic frequency is 40 kHz and the ultrasonic power is 100 W, and then drying them;
[0018] The post-treatment step includes: after the reaction is completed, centrifuging with a centrifuge, wherein the speed of the centrifuge is 7000-8000 rpm, the centrifugation time is 8-10 minutes, filtering, washing the precipitate with deionized water, and drying at a drying temperature of 40° C. for 20-24 hours to obtain functionalized aluminum oxide nanoparticles.
[0019] Pretreatment and post-treatment steps play a crucial role in the preparation of functionalized alumina nanoparticles. Pretreatment improves the dispersibility and surface activity of the particles through ultrasonic dispersion and drying, providing a good foundation for subsequent modification; while post-treatment ensures the purity and surface cleanliness of the particles through centrifugation, washing and drying, and maintains the integrity of the modified layer by controlling the drying conditions. Combining these steps, the performance of functionalized alumina nanoparticles is effectively improved, and its dispersibility, stability and responsiveness in polyurethane emulsion are optimized, thereby improving the overall performance of waterborne polyurethane emulsion.
[0020] The mechanical oscillation of ultrasound in pretreatment can overcome the van der Waals force between particles, reduce agglomeration, form a monodisperse system, and ensure that each particle is fully exposed to the subsequent chemical reaction environment, thereby improving the modification efficiency; and ultrasonic treatment can not only disperse the particles, but also remove the adsorbents and oxide layers on the surface of the particles, making the aluminum oxide surface more active. The increase in surface activity is conducive to the subsequent adsorption and chemical modification of polyvinyl alcohol, sodium polyacrylate and poly (N-isopropylacrylamide) to promote the uniformity and stability of surface modification; and the drying step can ensure that the particles will not agglomerate during the subsequent ethanol dispersion process, and no residual moisture will affect the reaction environment, thereby improving the efficiency of the entire modification process.
[0021] Centrifugal separation in post-treatment can effectively separate the functionalized nanoparticles generated after the reaction from the unreacted polymer and reaction by-products. Through high-speed centrifugation, the settled particles can be quickly collected to ensure the high purity of the particles, which is very important for the stability and performance of the nanoparticles in subsequent applications; washing with deionized water after centrifugation can further remove the unreacted substances or by-products remaining on the surface, ensure the surface is clean, and help improve the stability and dispersibility of the particles in the aqueous medium; and the drying step is carried out at a relatively low temperature (40°C), which can prevent the particles from agglomerating or the damage of the surface modification layer caused by high temperature, and maintain the integrity and functionality of the modification layer.
[0022] Furthermore, the polyisocyanate is diphenylmethane diisocyanate or isophorone diisocyanate; the polyol is polyether polyol or polyester polyol; the chain extender is ethylenediamine or 2,2-dihydroxymethylpropionic acid; the neutralizer is triethylamine; the organic solvent is acetone; and the catalyst is dibutyltin dilaurate.
[0023] Furthermore, the present invention also provides the use of the polyurethane emulsion described above in the preparation of coatings, adhesives or synthetic leather products.
[0024] Moreover, the present invention also provides a method for preparing the polyurethane emulsion as described above, comprising:
[0025] Step (1): Add polyol and organic solvent into a reaction kettle, stir evenly, then heat the reaction kettle to 60-80° C., add catalyst, stir evenly, and finally add polyisocyanate, react for 2-3 hours, stirring continuously during the reaction process, to obtain a prepolymer;
[0026] Step (2): first dissolving the chain extender in an organic solvent, then adding the mixture to the prepolymer obtained in step (1) while stirring, and continuing the reaction at 60-80° C. for 1-2 hours to obtain a reaction mixture; after the reaction is completed, adding a neutralizing agent to the reaction mixture to adjust the pH value to alkaline to obtain a neutralized prepolymer;
[0027] Step (3): Add functionalized alumina nanoparticles into 70-80°C water and stir evenly, then add the neutralized prepolymer obtained in step (2) into the water, stir, and then keep warm at 50-60°C for 10-30 minutes, cool, and obtain a polyurethane emulsion.
[0028] Furthermore, the neutralized prepolymer in step (3) is added into the water at a speed of 200-500 mL / min, and stirred at a speed of 1000-2000 rpm.
[0029] In the process of preparing polyurethane emulsion, it is very important to coordinate and control the addition speed and stirring speed of the neutralized prepolymer, which will directly affect the particle size distribution and stability of the emulsion. The present invention can obtain a uniform, stable, high-quality aqueous polyurethane emulsion by optimizing the addition speed and stirring speed of the neutralized prepolymer, and can also ensure its stable and excellent performance in applications such as coatings and adhesives. Since the neutralized prepolymer contains hydrophobic components of polyurethane, if the addition speed is too fast, the concentration in the local area will be very high, and the hydrophobic components will quickly aggregate in the water phase to form large particles or uneven emulsions, which will directly affect the stability and final performance of the emulsion. The present invention adopts the above-mentioned slow addition speed to ensure that the prepolymer is evenly dispersed and promote the formation of a small and stable emulsion. Secondly, since the stirring speed directly affects the shear force during the emulsification process, if the stirring speed is too low, the emulsion particles may be too large and easily sedimented or stratified, while if the stirring speed is too high, the emulsion may generate too much foam, affecting the stability of the emulsion. Therefore, the appropriate stirring speed is the key to balancing the uniformity and stability of the emulsion particles. The stirring speed of 1000-2000rpm in the present invention can provide sufficient shear force for the system to refine the neutralized prepolymer into tiny droplets, and ensure that the particles are refined and evenly distributed in the water phase to form a stable emulsion.
[0030] Compared with the prior art, the polyurethane emulsion provided by the present invention and its preparation method and application have the following advantages:
[0031] (1) The functionalized aluminum oxide nanoparticles of the present invention not only have a large specific surface area and surface energy, but also have hydrophilic functional groups on the surface of the functionalized aluminum oxide nanoparticles. These functional groups can form chemical bonds or strong physical adsorption with the polyurethane matrix or other components in the emulsion, thereby forming a strong interaction force in the aqueous polyurethane emulsion. When the functionalized aluminum oxide nanoparticles are dispersed in the aqueous polyurethane emulsion, they will form a three-dimensional spatial physical network structure in the emulsion through interaction and dispersion. The network structure can "capture" the polyurethane particles at a specific position, reducing the free movement of the particles in the emulsion; secondly, the network structure can also increase the viscosity of the emulsion, making the emulsion more stable in a static state, less prone to stratification and sedimentation, thereby effectively slowing down the sedimentation rate of the particles, reducing the stratification phenomenon in the emulsion, and thus improving the stability of the emulsion. Moreover, the aluminum oxide nanoparticles modified with polyvinyl alcohol, sodium polyacrylate and poly (N-isopropylacrylamide) can not only use their surface properties to adjust the interfacial tension in the emulsion and reduce the interfacial energy between the aqueous phase and the organic phase, thereby inhibiting the occurrence of phase separation; they can also protect the aqueous polyurethane emulsion at different temperatures and different acid-base environments, prevent the aggregation and agglomeration of polyurethane particles, avoid the instability and separation of the aqueous polyurethane emulsion, and greatly improve the long-term storage stability of the emulsion.
[0032] (2) During the drying process of the aqueous polyurethane emulsion, the surface of the functionalized aluminum oxide nanoparticles of the present invention will undergo a temperature-responsive transformation as the drying temperature changes. As the temperature rises, the functionalized aluminum oxide nanoparticles will become hydrophobic, thereby enhancing the hydrophobicity of the aqueous polyurethane emulsion, thereby prompting water to be discharged from the aqueous polyurethane emulsion more quickly, thereby increasing the drying speed. This successfully overcomes the problem in the prior art that the storage stability of the aqueous polyurethane emulsion is improved by enhancing the hydrophilicity of the polyurethane, which will lead to a decrease in the drying rate of the aqueous polyurethane emulsion.
[0033] (3) The present invention not only prepares water-based polyurethane emulsion by using mild solvents and catalysts, such as deionized water, ethanol, HCl and NaOH, but also uses low-temperature reaction conditions. For example, most of the reaction temperatures involved are between 30-80°C, which not only reduces energy consumption but also reduces thermal pollution to the environment. The final product belongs to an aqueous system, which reduces the emission of volatile organic compounds (VOCs), is more beneficial to air quality and human health, has more green and environmentally friendly advantages, and reduces environmental pollution and energy consumption. DETAILED DESCRIPTION
[0034] The present invention is further illustrated below through the description of specific implementation methods, but this is not a limitation of the present invention. Those skilled in the art can make various modifications or improvements based on the basic idea of the present invention, but as long as they do not deviate from the basic idea of the present invention, they are all within the protection scope of the present invention.
[0035] In the following examples and comparative examples, the methods used are all prior art unless otherwise specified; the reagents not otherwise specified are conventional reagents and can be purchased from conventional reagent production and sales companies. The information of some raw material manufacturers is as follows:
[0036] Polybutylene adipate, CAS No.: 150923-12-9, molecular weight: 2000, hydroxyl value 53-59 mg KOH / g, viscosity 700 mPa·S (75°C);
[0037] Polycaprolactone triol, CAS number: 37625-56-2, molecular weight: 3000;
[0038] Polyvinyl alcohol, CAS number: 9002-89-5, purchased from Jinan Sunny Chemical Technology Co., Ltd., brand number 24-88;
[0039] Sodium polyacrylate, CAS number: 9003-04-7, purchased from Hebei Runbu Biotechnology Co., Ltd., catalog number 34647;
[0040] Poly(N-isopropylacrylamide), CAS No.: 25189-55-3, was purchased from Hubei Tosoh Chemical Technology Co., Ltd.;
[0041] Dibutyltin dilaurate, CAS number: 77-58-7;
[0042] Acetone, CAS No.: 67-64-1;
[0043] Diphenylmethane diisocyanate, CAS number: 101-68-8;
[0044] Isophorone diisocyanate, CAS number: 4098-71-9;
[0045] Ethylenediamine, CAS No.: 107-15-3;
[0046] 2,2-Dihydroxymethylpropionic acid, CAS No.: 4767-03-7;
[0047] Triethylamine, CAS number: 121-44-8.
[0048] Example 1
[0049] Preparation of functionalized alumina nanoparticles:
[0050] First, 40 g of aluminum oxide nanoparticles with an average particle size of 30 nm were dispersed in 500 mL of deionized water, and treated with an ultrasonic processor for 30 min, wherein the ultrasonic frequency was 40 kHz and the ultrasonic power was 100 W, and then the aluminum oxide nanoparticles were dried; then the aluminum oxide nanoparticles were dispersed in 60 mL of ethanol, and then 20 g of polyvinyl alcohol was added and 1 M of acidic catalyst HCl was added dropwise to adjust the pH value to 4, and the reaction was stirred at a speed of 500 rpm, the reaction temperature was 60 ° C, and the reaction time was 3 h to obtain a suspension; after the reaction was completed, the temperature of the suspension was lowered to room temperature, and then concentrated The pH value was adjusted to 7 with 1M alkaline catalyst NaOH, 10g sodium polyacrylate was added, and the mixture was stirred at 600rpm for 1h; after the reaction, the temperature was raised to 30°C, 10g poly(N-isopropylacrylamide) was added, and the mixture was stirred at 600rpm for 1h. After the reaction, the mixture was centrifuged at a speed of 7000rpm and a centrifugal time of 8min, filtered, and the precipitate was washed with deionized water and dried at 40°C for 20h to obtain functionalized alumina nanoparticles.
[0051] Preparation of polyurethane emulsion:
[0052] Step (1): add 50 parts of polybutylene adipate and 10 parts of organic solvent acetone into a reaction kettle, stir evenly, then heat the reaction kettle to 60° C., add 0.01 parts of catalyst dibutyltin dilaurate, stir evenly, and finally add 35 parts of isophorone diisocyanate, react for 2 hours, and continue stirring at a speed of 800 rpm during the reaction process to obtain a prepolymer;
[0053] Step (2): first dissolving 3 parts of chain extender ethylenediamine in 7 parts of organic solvent acetone, then adding the mixture to the prepolymer obtained in step (1) while stirring, and continuing to react at 60° C. for 1 hour to obtain a reaction mixture; after the reaction is completed, adding 1 part of neutralizer triethylamine to the reaction mixture to adjust the pH value to alkaline, thereby obtaining a neutralized prepolymer;
[0054] Step (3): Add 3 parts of functionalized alumina nanoparticles into 200 parts of 70°C water and stir evenly, then add the neutralized prepolymer obtained in step (2) into the water at a rate of 250 mL / min, stir at a rate of 1000 rpm, then keep warm at 60°C for 10 minutes, cool, and obtain a polyurethane emulsion.
[0055] Example 2
[0056] Preparation of functionalized alumina nanoparticles:
[0057] First, 70 g of aluminum oxide nanoparticles with an average particle size of 50 nm were dispersed in 500 mL of deionized water, and treated with an ultrasonic processor for 30 min, wherein the ultrasonic frequency was 40 kHz and the ultrasonic power was 100 W, and then the aluminum oxide nanoparticles were dried; then the aluminum oxide nanoparticles were dispersed in 70 mL of ethanol, and then 30 g of polyvinyl alcohol was added and 1 M of acidic catalyst HCl was added dropwise to adjust the pH value to 5, and the reaction was stirred at a speed of 500 rpm, the reaction temperature was 65 ° C, and the reaction time was 4 h to obtain a suspension; after the reaction was completed, the temperature of the suspension was lowered to room temperature, and then a concentration of The pH value is adjusted to 8 with 1M alkaline catalyst NaOH, 15g sodium polyacrylate is added, and the reaction is stirred at a speed of 600rpm for 2h; after the reaction, the temperature is raised to 40°C, 15g poly (N-isopropylacrylamide) is added, and the reaction is stirred at a speed of 600rpm for 2h. After the reaction, centrifugal separation is performed using a centrifuge, wherein the speed of the centrifuge is 8000rpm, the centrifugal time is 10min, and the precipitate is filtered, washed with deionized water, and dried at a drying temperature of 40°C and a drying time of 24h to obtain functionalized alumina nanoparticles.
[0058] Preparation of polyurethane emulsion:
[0059] Step (1): add 70 parts of polybutylene adipate and 13 parts of organic solvent acetone into a reaction kettle, stir evenly, then heat the reaction kettle to 80° C., add 0.05 parts of catalyst dibutyltin dilaurate, stir evenly, and finally add 50 parts of isophorone diisocyanate, react for 3 hours, and continue stirring at a speed of 800 rpm during the reaction process to obtain a prepolymer;
[0060] Step (2): first dissolving 5 parts of chain extender ethylenediamine in 7 parts of organic solvent acetone, then adding the mixture to the prepolymer obtained in step (1) while stirring, and continuing to react at 80° C. for 2 hours to obtain a reaction mixture; after the reaction is completed, adding 2 parts of neutralizer triethylamine to the reaction mixture to adjust the pH value to alkaline, thereby obtaining a neutralized prepolymer;
[0061] Step (3): Add 5 parts of functionalized alumina nanoparticles into 300 parts of 80°C water and stir evenly, then add the neutralized prepolymer obtained in step (2) into the water at a rate of 350 mL / min, stir at a rate of 2000 rpm, then keep warm at 60°C for 30 minutes, cool, and obtain a polyurethane emulsion.
[0062] Example 3
[0063] Preparation of functionalized alumina nanoparticles:
[0064] First, 50 g of aluminum oxide nanoparticles with an average particle size of 40 nm were dispersed in 500 mL of deionized water, and treated with an ultrasonic processor for 30 min, wherein the ultrasonic frequency was 40 kHz and the ultrasonic power was 100 W, and then the aluminum oxide nanoparticles were dried; then the aluminum oxide nanoparticles were dispersed in 60 mL of ethanol, and then 25 g of polyvinyl alcohol was added and 1 M of acidic catalyst HCl was added dropwise to adjust the pH value to 4, and the reaction was stirred at a speed of 500 rpm, the reaction temperature was 65 ° C, and the reaction time was 4 hours to obtain a suspension; after the reaction was completed, the temperature of the suspension was lowered to room temperature, and then a concentration of The pH value is adjusted to 8 with 1M alkaline catalyst NaOH, 10g sodium polyacrylate is added, and the reaction is stirred at a speed of 600rpm for 2h; after the reaction, the temperature is raised to 35°C, 10g poly (N-isopropylacrylamide) is added, and the reaction is stirred at a speed of 600rpm for 2h. After the reaction, centrifugal separation is performed using a centrifuge, wherein the speed of the centrifuge is 8000rpm, the centrifugal time is 10min, and the precipitate is filtered, washed with deionized water, and dried at a drying temperature of 40°C and a drying time of 24h to obtain functionalized alumina nanoparticles.
[0065] Preparation of polyurethane emulsion:
[0066] Step (1): add 60 parts of polycaprolactone triol and 10 parts of organic solvent acetone into a reaction kettle, stir evenly, then heat the reaction kettle to 70° C., add 0.03 parts of catalyst dibutyltin dilaurate, stir evenly, and finally add 40 parts of diphenylmethane diisocyanate, react for 3 hours, and stir continuously at a speed of 800 rpm during the reaction process to obtain a prepolymer;
[0067] Step (2): first dissolving 4 parts of a chain extender 2,2-dihydroxymethylpropionic acid in 7 parts of an organic solvent acetone, and then adding the mixture to the prepolymer obtained in step (1) while stirring, and continuing to react at 70° C. for 1-2 hours to obtain a reaction mixture; after the reaction is completed, adding 1.5 parts of a neutralizing agent triethylamine to the reaction mixture to adjust the pH value to alkaline, thereby obtaining a neutralized prepolymer;
[0068] Step (3): Add 4 parts of functionalized alumina nanoparticles into 300 parts of 70°C water and stir evenly, then add the neutralized prepolymer obtained in step (2) into the water at a rate of 450 mL / min, stir at a rate of 2000 rpm, then keep warm at 60°C for 20 minutes, cool, and obtain a polyurethane emulsion.
[0069] Comparative Example 1
[0070] The difference from Example 3 is that sodium polyacrylate is not used to modify the aluminum oxide nanoparticles during the preparation of the functionalized aluminum oxide nanoparticles; the other steps and preparation process are the same as those of Example 3.
[0071] Preparation of functionalized alumina nanoparticles:
[0072] First, 50 g of aluminum oxide nanoparticles with an average particle size of 40 nm were dispersed in 500 mL of deionized water, and treated with an ultrasonic processor for 30 min, wherein the ultrasonic frequency was 40 kHz and the ultrasonic power was 100 W, and then the aluminum oxide nanoparticles were dried; then the aluminum oxide nanoparticles were dispersed in 60 mL of ethanol, and then 25 g of polyvinyl alcohol was added, and 1 M of acidic catalyst HCl was added dropwise to adjust the pH value to 4, and the reaction was stirred at a speed of 500 rpm, the reaction temperature was 65 ° C, and the reaction time was 4 hours to obtain a suspension; the reaction After completion, the temperature of the suspension was lowered to room temperature, and then 1M alkaline catalyst NaOH was added to adjust the pH value to 8, the temperature was raised to 35°C, 10g poly (N-isopropylacrylamide) was added, and the reaction was stirred at a speed of 600rpm for 2h. After the reaction was completed, centrifugal separation was performed using a centrifuge, wherein the speed of the centrifuge was 8000rpm, the centrifugal time was 10min, and the precipitate was filtered and washed with deionized water, and dried at a drying temperature of 40°C for 24h to obtain functionalized alumina nanoparticles.
[0073] Comparative Example 2
[0074] The difference from Example 3 is that poly(N-isopropylacrylamide) is not used to modify the aluminum oxide nanoparticles during the preparation of the functionalized aluminum oxide nanoparticles; the other steps and preparation process are the same as those of Example 3.
[0075] Preparation of functionalized alumina nanoparticles:
[0076] First, 50g of aluminum oxide nanoparticles with an average particle size of 40nm are dispersed in 500mL of deionized water, and treated with an ultrasonic processor for 30min, wherein the ultrasonic frequency is 40kHz and the ultrasonic power is 100W, and then the aluminum oxide nanoparticles are dried; then the aluminum oxide nanoparticles are dispersed in 60mL of ethanol, and then 25g of polyvinyl alcohol is added and 1M of acidic catalyst HCl is added dropwise to adjust the pH value to 4, and the suspension is stirred at a speed of 500rpm for reaction, the reaction temperature is 65°C, and the reaction time is 4h to obtain a suspension; after the reaction, the temperature of the suspension is lowered to room temperature, and then 1M of alkaline catalyst NaOH is added dropwise to adjust the pH value to 8, 10g of sodium polyacrylate is added, and the suspension is stirred at a speed of 600rpm for reaction, and the reaction time is 2h. After the reaction, centrifugal separation is performed using a centrifuge, wherein the speed of the centrifuge is 8000rpm, the centrifugal time is 10min, and the precipitate is washed with deionized water and dried at a drying temperature of 40°C and a drying time of 24h to obtain functionalized aluminum oxide nanoparticles.
[0077] Comparative Example 3
[0078] The difference from Example 3 is that the preparation step (3) of the polyurethane emulsion is: adding 4 parts of functionalized alumina nanoparticles to 300 parts of 70°C water and stirring evenly, then adding the neutralized prepolymer obtained in step (2) into the water at a rate of 1 L / min, and stirring at a speed of 800 rpm, then keeping warm at 60°C for 20 minutes, cooling, and obtaining the polyurethane emulsion. The other steps and preparation process are the same as those in Example 3.
[0079] Test example: performance test
[0080] 1. Test materials: polyurethane emulsions prepared in each group of the examples and comparative examples of the present invention.
[0081] 2. Test methods:
[0082] (1) Drying time test: Under the conditions of temperature of 35°C and humidity of 50±10%, the polyurethane emulsions prepared in each group of Examples 1-3 and Comparative Examples 1-3 were coated on an aluminum plate with a wire rod coater to prepare a coating film. The coating area was (100×50) mm. The coating completion time was recorded. After standing for a period of time, the coating film was cut with a blade within a range of not less than 10 mm from the edge of the specimen. If there was no finger adhesion on the bottom layer and the inside of the film, the drying was completed. The recorded time was the drying time. The test results are shown in Table 1.
[0083] Table 1 Drying time test results
[0084] Group Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Drying time 60min 71min 83min 116min 129min 105min
[0085] As shown in Table 1, the drying time test results of the polyurethane emulsion obtained by the embodiments of the present invention are all good, while the drying time of each group of comparative examples is affected to varying degrees. For example, the drying time of comparative example 1 is as long as 116 minutes. This is because comparative example 1 does not use sodium polyacrylate to modify the aluminum oxide nanoparticles, so that the electrostatic repulsion between the aluminum oxide nanoparticles is weakened, and the particles may condense in the system to form larger aggregates, which leads to uneven distribution of water in the emulsion and uneven thickness of the coating film, which increases the difficulty of evaporation of water from the inside of the aggregate during the drying process and prolongs the drying time. Comparative example 2, which does not use poly (N-isopropylacrylamide) to modify the aluminum oxide nanoparticles, has a drying time of up to 129 minutes. This is enough to show that after the aluminum oxide nanoparticles are modified by poly (N-isopropylacrylamide), the molecular chain will shrink during the drying process, resulting in changes in the surface structure of the particles, which can not only improve the dispersibility of the particles during the drying process, but also help the water evaporate quickly from the system, thereby affecting the drying speed of the emulsion. Secondly, in Comparative Example 3, in which the speed of adding the neutralized prepolymer to water and the stirring speed were adjusted, the drying time was also as long as 105 min. This indicates that the addition speed of the neutralized prepolymer is too fast and the reduction of the stirring rate will make it difficult for the prepolymer to be fully mixed in water, which may form larger particle agglomerates and reduce the uniformity between the nanoparticles and the polymer, which ultimately directly affects the evaporation of water in the drying process and prolongs the drying time.
[0086] (2) Storage stability test:
[0087] ① Thermal stability test:
[0088] The four-necked flasks containing the polyurethane emulsions prepared in each group of Examples and Comparative Example 2 were placed in a water bath, stirred for 24 hours at 10°C, 20°C, 30°C, 40°C, and 50°C, respectively, and allowed to stand to observe and record the changes in the polyurethane emulsions; then each group of polyurethane emulsions was adjusted to 25°C and stirred for 20 minutes, and then placed in a 50mL (10cm long) centrifuge tube for centrifugation at a speed of 3000 rpm for 30 minutes, taken out, and the changes in the polyurethane emulsions were observed. The test results are shown in Table 2.
[0089] Table 2 Thermal stability test results
[0090]
[0091] As shown in Table 2, the thermal stability test results of the polyurethane emulsions prepared in the embodiments of the present invention are all good. Although the polyurethane emulsions in each group showed coagulation after being placed at 40°C and 50°C for a period of time, after the polyurethane emulsions were placed at 25°C again, the polyurethane emulsions were able to recover as before, without stratification, coagulation or precipitation, which provides potential for the polyurethane emulsions to cope with extreme storage environments. However, after the polyurethane emulsions obtained in Comparative Example 2 showed coagulation at 40°C and 50°C, they could not be restored when placed at 25°C again, which further illustrates that the modification treatment of the present invention gives the aluminum oxide nanoparticles excellent temperature response characteristics, so that they exhibit controllable response behavior during use.
[0092] ②Acid-base stability test:
[0093] 50 mL of the polyurethane emulsion prepared in each group of Examples and Comparative Example 1 were respectively placed in a beaker, and then the pH value of the polyurethane emulsion was first adjusted to 4 with a 1M HCl solution and allowed to stand for 30 minutes; then the pH value of the polyurethane emulsion was adjusted to 7 with a 1M NaOH solution and allowed to stand for 30 minutes; finally, the pH value of the polyurethane emulsion was adjusted to 9 with a 1M NaOH solution and allowed to stand for 30 minutes, and the changes of the polyurethane emulsion at different pH values were observed. The test results are shown in Table 3.
[0094] Table 3 Acid-base stability test results
[0095]
[0096] As shown in Table 3, the acid-base stability test results of the polyurethane emulsions prepared in the embodiments of the present invention are all good, and no stratification, coagulation or precipitation occurs between pH values of 4-9. In the preparation process of Comparative Example 1, sodium polyacrylate was not used to modify the aluminum oxide nanoparticles, and instability, such as stratification, coagulation or precipitation, also occurred under acidic and alkaline conditions. This is because in an acidic environment, the polyurethane segments in the emulsion are charged due to protonation, resulting in a weakened charge shielding effect, an increased interaction force between particles, and a tendency for particle aggregation to occur; while in an alkaline environment (pH value of 9), although the molecular chains of the polyurethane in the system undergo a deprotonation reaction, the molecular chains carry a negative charge, resulting in an enhanced electrostatic repulsion, but the repulsion between the particles is not enough to completely offset other forces (such as hydrogen bonding, etc.), resulting in a slight coagulation of the emulsion at a higher pH value.
[0097] In summary, the aluminum oxide nanoparticles modified by polyvinyl alcohol, sodium polyacrylate, and poly (N-isopropylacrylamide) in the present invention can not only enhance the compatibility of polyurethane with solvent water and inhibit the occurrence of phase separation, but also protect the aqueous polyurethane emulsion under different temperatures and different acid-base environments, prevent the aggregation and agglomeration between polyurethane particles, avoid the instability and separation of the aqueous polyurethane emulsion, and greatly improve the long-term storage stability of the emulsion. In addition, during the drying process of the aqueous polyurethane emulsion, the surface of the functionalized aluminum oxide nanoparticles of the present invention will undergo a temperature-responsive transformation as the drying temperature changes. As the temperature rises, the hydrophobicity of the aqueous polyurethane emulsion will be enhanced, thereby prompting water to be discharged from the aqueous polyurethane emulsion faster, thereby increasing the drying speed, successfully overcoming the problem in the prior art that the storage stability of the aqueous polyurethane emulsion is improved by enhancing the hydrophilicity of the polyurethane, which will lead to a decrease in the drying rate of the aqueous polyurethane emulsion.
[0098] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A polyurethane emulsion, characterized in that: The invention comprises the following raw materials in parts by weight: 35-50 parts of polyisocyanate, 50-70 parts of polyol, 3-5 parts of chain extender, 1-2 parts of neutralizer, 200-300 parts of water, 10-20 parts of organic solvent, 0.01-0.05 parts of catalyst and 3-5 parts of functionalized alumina nanoparticles; The preparation method of the functionalized aluminum oxide nanoparticles comprises: dispersing the aluminum oxide nanoparticles in a solvent, then adding polyvinyl alcohol and dropping an acid catalyst to adjust the pH value to 4-5, and then stirring to react, the reaction temperature is 60-65° C., and the reaction time is 3-4 h to obtain a suspension; after the reaction is completed, the temperature of the suspension is lowered to room temperature, and then a basic catalyst is added to adjust the pH value to 7-8, and then sodium polyacrylate is added, and stirred to react, and the reaction time is 1-2 h; after the reaction is completed, the temperature is raised to 30-40° C., poly(N-isopropylacrylamide) is added, and stirred to react, and the reaction time is 1-2 h to obtain functionalized aluminum oxide nanoparticles.
2. The polyurethane emulsion according to claim 1, characterized in that The acidic catalyst is HCl; the alkaline catalyst is NaOH.
3. The polyurethane emulsion according to claim 1, characterized in that The mass ratio of the aluminum oxide nanoparticles to polyvinyl alcohol, sodium polyacrylate and poly(N-isopropylacrylamide) is (4-7):(2-3):(1-1.5):(1-1.5).
4. The polyurethane emulsion according to claim 1, characterized in that The solvent is ethanol; the dosage ratio of the aluminum oxide nanoparticles to the solvent is 1 g: 10-15 mL.
5. The polyurethane emulsion according to claim 1, characterized in that The method for preparing the functionalized aluminum oxide nanoparticles further comprises the steps of pre-treatment and post-treatment of the aluminum oxide nanoparticles: The aluminum oxide nanoparticle pretreatment step comprises: dispersing the aluminum oxide nanoparticles in deionized water, treating them with an ultrasonic processor for 30 minutes, wherein the ultrasonic frequency is 40 kHz and the ultrasonic power is 100 W, and then drying them; The post-treatment step includes: after the reaction is completed, centrifuging with a centrifuge, wherein the speed of the centrifuge is 7000-8000 rpm, the centrifugation time is 8-10 minutes, filtering, washing the precipitate with deionized water, and drying, the drying temperature is 40° C., and the drying time is 20-24 hours, to obtain functionalized aluminum oxide nanoparticles.
6. The polyurethane emulsion according to claim 1, characterized in that The polyisocyanate is diphenylmethane diisocyanate or isophorone diisocyanate; the polyol is polyether polyol or polyester polyol; the chain extender is ethylenediamine or 2,2-dihydroxymethylpropionic acid; the neutralizer is triethylamine; the organic solvent is acetone; and the catalyst is dibutyltin dilaurate.
7. Use of the polyurethane emulsion according to any one of claims 1 to 6 in the preparation of coatings, adhesives or synthetic leather products.
8. The method for preparing a polyurethane emulsion according to any one of claims 1 to 6, characterized in that: include: Step (1): Add polyol and organic solvent into a reaction kettle, stir evenly, then heat the reaction kettle to 60-80°C, add catalyst, stir evenly, and finally add polyisocyanate, react for 2-3 hours, stirring continuously during the reaction process, to obtain a prepolymer; Step (2): first dissolving the chain extender in an organic solvent, then adding the mixture to the prepolymer obtained in step (1) while stirring, and continuing the reaction at 60-80° C. for 1-2 h to obtain a reaction mixture; after the reaction is completed, adding a neutralizing agent to the reaction mixture to adjust the pH value to alkaline to obtain a neutralized prepolymer; Step (3): Add the functionalized alumina nanoparticles into 70-80°C water and stir evenly, then add the neutralized prepolymer obtained in step (2) into the water and stir, then keep the water at 50-60°C for 10-30 minutes, cool, and obtain a polyurethane emulsion.
9. The method for preparing a polyurethane emulsion according to claim 8, wherein The neutralized prepolymer in step (3) is added to the water at a rate of 200-500 mL / min, and stirred at a speed of 1000-2000 rpm.
Citation Information
Patent Citations
Chromium-free surface treatment liquid for zinc-iron alloy coated steel plate and preparation method of chromium-free surface treatment liquid
CN117867483A
Water-based carbon nanofluid and preparation method thereof
CN109054791A
Alumina dispersion liquid compatible with anion system and preparation method thereof
CN114456737A